Penerapan Sanksi Pidana Bagi Pelaku Tindak Pidana Penggelapan Uang Cash On Delivery dalam Putusan Pengadilan Nomor: 139/Pid.B/2020/PN.Amb - Devi Neng Hartanti; Juanrico Alfaromona Sumarezs Titahelu; Iqbal Taufik (Faculty of Law, Universitas Pattimura, 2021)
Introduction: The criminal act of embezzlement by weight, namely where the perpetrator of the wrongdoing or the act is very diverse. Not only taking money and making false reports, but the perpetrators also have a burden of responsibility in the form of special elements that are burdensome and also family. This article analyzes the application of criminal law against the perpetrators of embezzlement of cash on delivery (COD) in court decision number 139/Pid.B/2020/PN.Amb.Purposes of the Research: This writing aims to analyze and discuss the legal considerations of the judge in making a verdict on the criminal act of embezzling Cash On Delivery (COD).Methods of the Research: The research method in this writing uses a normative juridical research type because the focus of the study departs from the analysis of the judge's decision, using the following approaches: statute approach and case approach. Legal material collection techniques use library research techniques, as well as legal material analysis techniques in this study using qualitative analysis techniques.Results of the Research: Based on the results of the research, it was found that the application of criminal law against the criminal act of embezzlement of cash on delivery (COD) in decision Number 139/Pid.B /2020/PN.Amb that the article charged by the public prosecutor against the defendant was Article 374 of the ciminal code. it has been proven that all the elements contained in the article have been fulfilled, the verdict handed down by the judge, namely imprisonment for 2 (two) years and 7 (seven) months, is lower than the criminal threat in the demands of the public prosecutor, namely 4 (four) 6 (six) months and Article 374 of the ciminal code, namely the maximum imprisonment of 5 (five) years. The legal basis for the judge's consideration in making a decision on the crime of embezzlement of cash on delivery (COD) in decision number 139/Pid.B/ 2020/PN.Amb is juridical and non-juridical considerations